Limit Theorems for k-sequences of independent Random variables - Petrov, V. V. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. В. Петров, Предельные теоремы для к-последовательностей независимых случайных величинV. Petrovas, Ribinės teoremos nepriklausomų atsitiktinių dydžių k-sekoms